Concentration-dependent effect of norfloxacin on iron toxicity in the intestine of large yellow croaker Larimichthys crocea (Richardson, 1846) - Zeng, Lin; Wang, Yong-Hong; Ai, Chun-Xiang; Liu, Bin; Yu, Min-Hui; Zhang, Hui; Li, Fei (Frontiers in Marine Science, 2025)
This study explores the effects of norfloxacin (NOR) on oxidative damage, iron (Fe) transport, energy metabolism, and immunotoxicity in the intestine of large yellow croaker under Fe stress. The fish were subjected to Fe (180 μg/L), low-dose NOR (1.8 μg/L, LNOR), high-dose NOR (180 μg/L, HNOR), Fe plus LNOR, and Fe plus HNOR for 60 days. These results demonstrated that Fe alone exposure increased malondialdehyde (MDA), protein carboxylation (PC), and mortality rate, and impaired intestinal tissue, which was related to the increment of Fe accumulation. Compared to Fe alone exposure, Fe plus LNOR exposure decreased MDA, PC, and mortality rate, and alleviated intestinal malformations by improving Fe transport, energy metabolism, anti-inflammatory response, and protein folding protective effect, and reducing pro-inflammatory response, indicating that LNOR had an antagonistic effect on Fe toxicity. Compared to Fe alone exposure, Fe plus HNOR exposure elevated MDA, PC, and mortality rate, and deteriorated intestinal malformations by inhibiting Fe excretion, energy metabolism, anti-inflammatory response, and protein folding protective effect, and enhancing pro-inflammatory response, indicating a synergetic effect between HNOR and Fe stress. These findings suggested that NOR had a dose-dependent effect on Fe-toxicity to large yellow croaker, which contributes to revealing the molecular mechanisms behind their interaction and its ecological implications.